Stress-related genetic components in attention-deficit/hyperactivity disorder (ADHD): Effects of the SERPINA6 and SERPINA1 genetic markers in a family-based brazilian sample. (May 2022) - Carpena, Marina Xavier; Sánchez-Luquez, Karen Yumaira; Martins-Silva, Thais; Santos, Thiago M; Farias, Cid Pinheiro; Leventhal, Daniel Gray Paschoal; Berruti, Barbara; Zeni, Cristian Patrick; Schmitz, Marcelo; Chazan, Rodrigo; Hutz, Mara H.; Salatino-Oliveira, Angélica; et al.
Abstract: SERPINA6 and SERPINA1 were recently identified as the main genes associated with plasma cortisol concentration in humans. Although dysregulation in the Hypothalamus–Pituitary-Adrenal (HPA) axis has been observed in Attention Deficit/Hyperactivity Disorder (ADHD), the molecular mechanisms underlying this relationship are still unclear. Evaluation of the SERPINA6/SERPINA1 gene cluster in ADHD may provide relevant information to uncover them. We tested the association between the SERPINA6/SERPINA1 locus, including 95 single nucleotide polymorphisms (SNPs), and ADHD, using data from a Brazilian clinical sample of 259 ADHD probands and their parents. The single SNP association was tested using binary logistic regression, and we performed Classification and Regression Tree (CART) analysis to evaluate genotype combinations' effects on ADHD susceptibility. We assessed SNPs' regulatory effects through the Genotype-Tissue Expression (GTEx) v8 tool, and performed a complementary look-up analysis in the largest ADHD GWAS to date. There was a suggestive association between ADHD and e ight variants located in the SERPINA6 region and one in the intergenic region between SERPINA6 and SERPINA1 after correction for multiple tests (p < 0.032). CART analysis showed that the combined effects of genotype GG in rs2144833 and CC in rs10129500 were associated with ADHD (OR = 1.78; CI95% = 1.24–2.55). The GTEx assigned the SNPs as eQTLs for genes in different tissues, including SERPINA6, and the look-up analysis revealed two SNPs associated with ADHD. These results suggest a shared genetic component between cortisol levels and ADHD. HPA dysregulation/altered stress response in ADHD might be mediated by upregulation of corticosteroid binding globulin (CBG, encoded by SERPINA6 ) expression. Highlights: HPA axis dysregulation, stress response dysfunction share genetic component with ADHD. SERPINA6 gene may be tied to ADHD and HPA dysregulation, stress response dysfunction. Interaction of rs2144833 and rs10129500 may imply variants' cumulative effect on ADHD. SERPINA6 SNPs' associations seem specific to ADHD, unhampered by anxiety comorbidity.